Adminducracy: The Dialectics of Power and Authority in Indonesia’s Local Governance - Frisher Maloringan, Julius; Robert Pinasang, Dani; Setiabudhi, Donna Okthalia; Jullie Pinori, Josepus; Kalalo , Merry Elisabeth (Advances In Social Humanities Research, 2025)
Population administration is a fundamental pillar in the implementation of effective, democratic, and data-driven governance. Within the framework of the Unitary State of the Republic of Indonesia (NKRI), the distribution of authority between central and regional governments follows the principles of decentralization, deconcentration, and co-administration. Although Law Number 24 of 2013 grants regional governments a role in providing population administration services—such as issuing electronic ID cards and birth certificates—the substantive control over policies and service standards remains centralized. This raises critical questions about the extent of regional autonomy in regulating population administration. Using a descriptive normative approach, this article analyzes the legal framework, the universal principles of civil registration, and the practical implementation across regions. The study concludes that strengthening functional autonomy and fostering balanced collaboration between central and local governments are essential to ensuring fairness, effectiveness, and sustainability in the delivery of civil registration services throughout Indonesia.